An Aboriginal youth suicide prevention project in rural Victoria. (2nd July 2016) - Isaacs, Anton; Sutton, Keith
ABSTRACT: Objective: To describe an Aboriginal youth suicide prevention project developed by Njernda Aboriginal Corporation. Method: This is a descriptive study of an Aboriginal youth suicide prevention project developed by Njernda Aboriginal Corporation based in Echuca, Victoria. Information about the program was obtained from interviewing the project worker and the social and emotional wellbeing worker. Further information was obtained about the program by examining activity registers, program flyers and posters. Results: The Aboriginal youth suicide prevention project was designed and implemented by Njernda Aboriginal Corporation over a period of three years. The main components of the project were building resilience, early intervention response and immediate postvention support. Resilience was built through the Bullroarer program, the Red Dust Healing program and community awareness programs. Another program, the Jekkora group was developed and implemented as an early intervention response. A postvention service is in the planning stage. Conclusions: During a three-year period Njernda Aboriginal Corporation established community resilience building and early intervention programs. Developing and implementing a comprehensive suicide prevention plan at the community level requires adequate time as well as support from mainstream services. These findings therefore have implications for future planning of Aboriginal suicide prevention projects.